The Influence of Online Customer Review and Online Customer Rating on Purchase Intention in TikTok Shop E-Commerce (A Study on TikTok Shop Online Consumers @Vivacosmetics) - Mazidah, Athaya Faza; Wijayanti, Rena Feri; Rachmi, Asminah (Jurnal Ekonomi, 2026)
The rapid growth of e-commerce has led to the rise of social commerce platforms, including TikTok Shop, which has experienced significant user expansion in Indonesia. Among the most rapidly growing product categories on TikTok Shop is beauty, particularly brands like Viva Cosmetics. Two key factors that influence consumer purchase interest in this context are online customer reviews and online customer ratings. Therefore, this study aims to examine the effect of online customer reviews (X1) and online customer ratings (X2) on consumer purchase interest (Y) in Viva Cosmetics products on TikTok Shop. This study employed a quantitative approach with a survey research design. The sampling method used was probability sampling with a proportionate stratified random sampling technique. The sample consisted of 100 respondents who were TikTok Shop users residing in Malang City and had seen or shown interest in Viva Cosmetics products. Data were collected through online questionnaires, and the analytical methods used included multiple linear regression and hypothesis testing to analyze the influence between the independent and dependent variables. The results of the study indicate that both online customer reviews (X1) and online customer ratings (X2) have a positive and significant effect on consumer purchase interest. The partial hypothesis test results show that each variable independently influences purchase interest positively and significantly. Furthermore, the simultaneous test results reveal that online customer reviews and online customer ratings together have a significant and positive impact on consumer purchase interest. Based on these findings, it can be concluded that Viva Cosmetics consumers on TikTok Shop exhibit high purchase interest influenced by online reviews and ratings. Therefore, business operators should pay attention to the quality of customer reviews and maintain high product ratings to increase product attractiveness and strengthen consumer trust.